Beyond profit: Reframing innovation capability through maslahah - Mohammad Sopian, NorAin; Pitchay, Anwar Allah (Journal of Islamic, Social, Economics and Development, 2026)
The resource-based view (RBV) remains a dominant theoretical lens in strategic management, explaining how firms achieve sustained competitive advantage through valuable, rare, inimitable, and non-substitutable (VRIN) resources. However, RBV has been increasingly criticised for its limited engagement with ethical, social, and welfare-oriented dimensions of organisational strategy. This viewpoint paper extends RBV by integrating Maslahah, the concept of public welfare rooted in Maqasid al-Shariah, as a strategic resource and capability. Drawing on both classical Islamic jurisprudence and contemporary management literature, the paper argues that Maslahah can be conceptualised as an intangible, value-driven organisational capability that enhances innovation outcomes. By embedding ethical and societal considerations into resource deployment, Maslahah strengthens the explanatory power of RBV in understanding innovation capability. The paper contributes theoretically by proposing Maslahah as both a VRIN resource and a mediating mechanism, and practically by guiding organisations toward sustainable and socially responsible innovation strategies.